(untitled) (Al-Academy, 2020)
Studying the past for its importance and connection with the present is reflected in a relative scale in the light of data and thought of the predecessors of a great nation like the Mesopotamia, where its civilization flourished and rose since the ancient times, which inspires the present with inherited meanings that might be an entity or recognized symbols in the establishment of a vision, system or architectural building. The researcher has crystallized the description of the past to enhance the vision of the present within what is required by the interior design specialty about the historical origins of education and the design of schools in the Mesopotamia, in addition to its ethnic and environmental specificity and the moral content, which is considered a direct reflection for a set of cultural and social ideas and values that were prevailing at that time. Mesopotamia is considered one of the civilizations that are concerned with the letter and writing. The cuneiform writing which originated since the Sumerians is one of the earliest writings created by humans. The research consists, in its theoretical framework, of two sections with the analysis of the design of Al-Mustansiriyyah school and Al-Sharabiyya school in Baghdad. Then a set of conclusions have been reached at clearly summarizing the objective data and the starting points including: the modern schools interior design products are characterized by new and unfamiliar formal values that distance themselves from the environmentally balanced design with certain limits in their appearance, as a result of not considering the designs of old schools. The research put some recommendations including: focusing on the designs of the heritage schools and the possibility of employing them as one of the successful designing methods in the aesthetic and functional expression.